Populations analysis of the Brazilian Sharpnose Shark Rhizoprionodon lalandii (Chondrichthyes: Carcharhinidae) on the São Paulo coast, Southern Brazil: inferences from mt DNA sequences - Mendonça, Fernando Fernandes [UNESP]; Oliveira, Claudio [UNESP]; Gadig, Otto Bismarck Fazzano [UNESP]; Foresti, Fausto [UNESP] (Sociedade Brasileira de Ictiologia, 2009)
Tubarões do gênero Rhizoprionodon são considerados predadores de grande importância ao longo da cadeia trófica nos ecossistemas costeiros e marinhos, também representando um importante recurso econômico para a pesca, especialmente no litoral brasileiro. A fim de analisar a estrutura populacional do tubarão Rhizoprionodon lalandii no litoral de São Paulo, sudeste do Brasil, foram identificados os níveis de diversidade genética a partir da análise de sequências nucleotídicas da região controladora do DNA mitocondrial. Os dados obtidos neste estudo apresentam valores moderados de diversidade haplotípica e baixos índices de diversidade nucleotídica. Embora os testes de AMOVA (ΦST = 0,08394, P < 0,01) tenham revelado uma pequena diferença entre as amostras estudadas, evidências sobre a ocorrência de estruturação populacional não foram encontradas o que pode representar uma característica geral para tubarões vivendo em áreas costeiras.

Sharks of the genus Rhizoprionodon can be considered some of the most important predators along the trophic coastal marine ecosystems and represent an important economic resource for the small-scale fisheries, especially on the Brazilian coastline. In order to analyze the population structure of the shark Rhizoprionodon lalandii of São Paulo, Southeastern coast of Brazil, levels of genetic diversity were identified by nucleotide sequence analyses of the mitochondrial DNA control region. The results obtained from this study present moderate values of haplotype diversity and low nucleotide diversity. Although the AMOVA tests (ΦST = 0.08394, P < 0.01) had shown slightly differences among the studied samples, evidence for the occurrence of population structuring was not found, which may be a general feature of sharks living in coastal areas.
Keywords: D-loop; Haplotypes; Mitochondrial control region; Shark conservation